PEMANFAATAN ARTIFICIAL INTELLIGENCE (AI) DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) BINA INSAN KAMIL - Machfud, Syaeful; Prasetia, Okky; Ibnurhus, Gigih Amrillah (JAMAIKA: JURNAL ABDI MASYARAKAT, 2025)
This community service program aims to enhance learning motivation and digital literacy of learners at PKBM Bina Insan Kamil through the utilization of Artificial Intelligence (AI) technology. The initial conditions indicated low learning motivation caused by work-related fatigue, limited learning methods, and minimal use of digital technology by tutors. Although most learners already owned digital devices such as smartphones, their digital literacy skills remained limited. Tutors also faced challenges in mastering AI-based learning applications, resulting in conventional and less engaging instructional practices. This program was designed through intensive training and mentoring on the use of ChatGPT, Canva AI, Duolingo AI, Gamma AI, and AI Generate as innovative and technology-driven learning solutions. The implementation stages included preparation, training, implementation assistance, and evaluation. The results demonstrated an increase in learners’ motivation, improved ability to utilize AI-based applications for learning, and enhanced tutor competence in developing more engaging digital learning materials. The application of gamification through Duolingo AI significantly increased learner participation and engagement. Furthermore, the digitalization of PKBM administrative processes positively impacted institutional management efficiency. Overall, this program successfully supported digital transformation in non-formal education and has strong potential for sustainable implementation. Keywords: artificial intelligence; learning motivation; digital literacy; PKBM; innovative learning